Financial institutions as an example of institutions of public trust - Agata Jakubowska (Managerial Economics)
Financial institutions are commonly known as institutions of public trust and they are fundamental for activities of other economic entities. The level of trust determines the competitive position of financial institutions. That is why care about the best standards is the most important task for these institutions. Financial institutions are called institutions of public trust and thus high professionalism and more responsibility is demanded from them. This article presents basic problems concerning trust and institutions of public trust. The article is also an attempt to verify the statement that financial institutions are institutions of public trust.